The Labour Market Returns to Graduation: Reconciling Administrative and Survey Data Estimates - Anna Adamecz; Matt Dickson; Nikki Shure (Institute of Labor Economics (IZA), 2024)
This paper contributes to the literature on the earnings returns to university graduation. Recent evidence using administrative earnings data from England suggests a zero return to graduation for men and positive returns to graduation for women in annual earnings at age 26. We show that once hours worked are taken into account - typically not available in administrative tax data - returns to graduation are zero for women too. Graduate women work more hours than comparable non-graduate women, explaining their annual earnings return, but in terms of hourly wages, average returns to graduation at this early career stage are around zero for both sexes. This highlights the importance of using both survey and administrative data sources when estimating the returns to university graduation.
Keywords: I23; I26; 330; returns to graduation; university; gender differences; survey data